Relationship between Lightning Flashes and Three Flash Flood Events in Malacca Malaysia - Roslan H.S.; Ahmad M.R.; Sumardi A.; Baharin S.A.S.; Yunus M.M.; Aris N.A.M.; Hwa H.Y.; Hidayah; Baharuddin M.Z.; Morimoto T.; Takayanagi Y.; Kawasaki Z.; et al. (VDE Verlag GmbH, 2025)
This study focuses on the analysis of lightning flashes (<30 km) and flash flood events that happened in Malacca Malaysia on October 20th, 2021, between 13:00 and 17:00 local time (UTC+8). Three flash flood events have been observed at three sites namely Kg. Sungai Putat (Site 1), Melaka International Trade Centre (Site 2), and Lebuh Raya Ayer Keroh Lama (Site 3). The observations of lightning activities were using a fast-antenna (FA) system, a constant altitude plan position indicator (CAPPI) radar echo, and cloud top height from Himawari-8 satellite image. The total number of detected lightning in this study is 208 flashes. Out of 208 flashes, 59 positive cloud-to-ground (+CG), 15 negative cloud-to-ground(-CG), 66 positive narrow bipolar event(+NBE), 7 negative bipolar event(-NBE), and 110 intracloud flashes have been identified. The highest reflectivity value was 53 dBZ recorded at Site 1 with estimated cloud top height (CTH) value of around 14 km. The relationship analysis between lightning activity and flash floods demonstrates that tropical thunderstorms generate a greater number of positive cloud-to-ground lightning strikes when cloud top reached 14 km. Moreover, there is a substantial correlation between lightning flash rate and the highest reflectivity value, which exceeds 50dBZ, at all three flash flood locations. Therefore, it is evident that persistent rainfall is a significant contributing factor to the occurrence of flash floods, even if the intensity of the rainfall is not particularly high. ? 2024 IEEE, ? VDE VERLAG GMBH Berlin Offenbach.